An aminophosphonate ester ligand-containing platinum(ii) complex induces potent immunogenic cell death in vitro and elicits effective anti-tumour immune responses in vivo. Issue 87 (1st October 2019) - Huang, Ke-Bin; Wang, Feng-Yang; Feng, Hai-Wen; Luo, Hejiang; Long, Yan; Zou, Taotao; Chan, Albert S. C.; Liu, Rong; Zou, Huahong; Chen, Zhen-Feng; Liu, Yan-Cheng; Liu, You-Nian; et al.
Abstract : A platinum(ii )-aminophosphonate complex (Pt1 ) induces potent anti-tumour immunogenic cell death (ICD) in vitro and in vivo . Abstract : A platinum(ii ) complex containing an aminophosphonate ligand preferentially accumulates in the endoplamic reticulum (ER) in association with potent ER stress and reactive oxygen species generation, followed by the activation of damage-associated molecular pattern signals and immune responses. Importantly, the Pt complex exhibits potent anti-tumour activities in two independent mouse models via an immunogenic cell death pathway.